Hazards inherent in interdisciplinary behavioral research. Issue 1 (December 2015) - Crews, David; Weisberg, Seth; Sarkar, Sahotra
Abstract Many, if not all, questions in biology and psychology today were formulated and considered in depth, though typically in a different language, from the 1700's to the early 1900's. However, because of politics or fashion, some topics fell out of favor or failed to recruit new scientists and hence languished. Despite greatly expanded scholarship in the history of the life sciences in the twentieth century, many such topics have had to be rediscovered in recent years, while much of the wisdom already accrued stays in the older literature and not in active minds. This is particularly true today when scientific advances appear at breakneck speed. It would not be an exaggeration to say that many 'breakthroughs' turn out really to be rediscoveries of forgotten observations. Two areas of particular significance to the interdisciplinary study of behavior are the Norms of Reaction (from Biology) and the concept of Plasticity (from Psychology). These and related fields benefit from the perspective of epigenetics so long as rigorous operational definitions are implemented. It is also important to revive Hogben's admonition that the interaction of hereditary and environment cannot be understood outside of the context of development. Five examples of increasing complexity in phenotypic plasticity in brain and behavior are presented to illustrate this perspective.